Clinical and metabolic correlates of women with polycystic ovary syndrome (PCOS) in a semi-urban community in Sri Lanka - Kumarapeli, V.; Seneviratne, R. De A.; Dodampahala, S.H.; Wijeyaratne, C.N. (My University, 2007)
Abstract INTRODUCTION:metabolic derangements associated with PCOS may predispose women to range of diseases with attendant morbidity and mortality risks: type 2 diabetes mellitus, hypertension, dyslipidaemia and metabolic syndrome.OBJECTIVE:to assess clinical and metabolic correlates of Sri Lankan women with PCOS. METHODS: A case control study was carried among 146 newly diagnosed women with PCOS detected by a community based cross sectional survey that screened 3030 women aged 15-39 years in the district of Gampaha, in 2005; and 170 age matched controls selected from the same community. PCOS case definition was based on Rotterdam 2003 revised diagnostic criteria. RESULTS: Delayed resumption of regular cycles following menarche occured 9.1 times (95 percent CI 5.52-15.0) and pubertal onset excess weight gain occured 2.48 times (95 percentCI 1.21-5.10) more frequently in the PCOS groupPrevalence of abdominal and generalized obesity was significantly higher (p<0.01) among cases than controls: abdominal obesity - waist hip ratio WHR>0.85 was 57.1percent (PCOS) vs 41.2percent (controls); generalized obesity - BMI 25 was 43.5percent (PCOS) vs 26.5percent (controls). WHR >0.85 occurred 1.9 (95percentCI 1.22-2.98) times and BMI 25 occurred 2.14 (95percentCI 1.34-3.43) times among cases than controls. Cases had significantly higher (p<0.001) mean fasting plasma insulin level 7.2 - u/ml; (PCOS) vs, 5.8 _u/ ml (controls). Prevalence of abnormal triglycerides (19.7percent vs 8.8percent), abnormal LDL (17.7percent vs 7.1percent), hypertension (10.9percent vs 4.1percent). and the metabolic syndrome (31.3percentvs 17.1percent) was also significantly higher (p<0.05) among cases than controls: CONCLUSIONS AND RECOMMENDATIONS: PCOS has long term effects on the metabolic status of affected women especially metabolic syndrome. Greater care is essential from the time of their diagnosis.
Keywords: POLYCYSTIC OVARY SYNDROME (PCOS); METABOLIC SYNDROME; Sri Lanka